Growth and yield response of Edamame soybean plants (Glycine max L.) to application of straw mulch and PGPR (Plant Growth Promoting Rhizobacteria) - Karomah, Khusnil; Rr. Liliek Dwi Soelaksini; Christa Dyah Utami; Tirto Wahyu Widodo (KHD Production, 2025)
Soil microorganism activity is inhibited during the dry season, especially in dry land. Mulching is one of the efforts to maintain soil moisture and microorganism activity. This study aims to examine the growth response plant edamame against the use of mulch straw and application PGPR (Plant Growth Promoting Rhizobacteria). Conducted from July to September 2024 in Kaliurang Village, Jember with an altitude of 146 meters above sea level. This experiment was designed using factorial RAK consisting of two factors and three replications. Factor First that is concentration PGPR Which consists of from 0 ml/l (control), 12.5 ml/l and 25 ml/l, while the second factor is the thickness of straw mulch consisting of 2.5 cm, 4.5 cm, And 6.5 cm. Results study This show existence interaction from PGPR And mulch straw on treatment mulch 6.5 cm + 12.5 ml/l with tall 17.30 cm 24 HST. In the treatment (4.5 cm + PGPR 12.5 ml/l) it influenced the height plant age 32 HST (23.00 cm), amount pod per sample 20.13 pod and biomass dry18.53 g, whereas amount branch per sample on treatment (0 ml/l + 6.5 cm) 1.93 branches. However, the weight of pods per sample and the weight of pods per plot did not happen interaction. Heavy pod per sample on concentration 25 ml/l (55.02 g), at a mulch thickness of 4.5 cm (54.31 g). Pod weight per plot 1255.89 g (25 ml/l) and 1253.22 (4.5 cm). Use mulch straw allegedly capable guard humidity soil so that the microorganisms in PGPR are able to grow well and activity microorganisms in a way can directly influence growth and edamame crop yields.